Spiritual Well-Being as a Predictor of Muslim Teachers’ Performance in Indonesia: Educational Implications - Agustin, Liliza; Wan Husin, Wan Nurul Izza (International Journal of Pedagogy and Learning Community (IJPLC), 2025)
Spiritual well-being serves not only as a foundation for inner peace but also plays a crucial role in enhancing teacher performance. This quantitative study aims to empirically examine the predictive role of spiritual well-being on the performance of Muslim teachers in Indonesia using Structural Equation Modeling (SEM). Data were collected from 606 Muslim teachers, and psychometric analysis confirmed the validity and reliability of the instruments. The SEM results demonstrated that spiritual well-being significantly predicts teacher performance (p-value = 0.030 < α 0.050), with the measurement model meeting all fit criteria. These findings enrich the field of educational psychology by highlighting the interconnection between spiritual and professional dimensions. Practically, the study suggests that education policies and teacher training programs should incorporate spiritual well-being as part of a holistic approach to professional development. Furthermore, the integration of spiritual dimensions may foster higher motivation, emotional resilience, and ethical commitment among teachers, which are vital for sustaining educational quality. For broader visibility, this research underscores the importance of addressing spiritual aspects in educational settings, particularly within Indonesia’s cultural and religious context, thereby contributing to a more balanced and humanistic model of teacher performance.